Ekstrak Daun Kelor Melancarkan Air Susu Ibu Postpartum di Puskesmas Kassi-Kassi - Hasbiah Wardani; Mirna Mirna (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
During the postpartum period, one of the most important things is how the postpartum mother is able to excrete breast milk smoothly. The purpose of this study was to analyze the effect of Moringa leaf extract on the smoothness of breast milk in postpartum mothers at the Kassi-Kassi Public Health Center. The design of this research was posttest only with control group. The research sample was 40 postpartum mothers who were selected by purposive sampling technique. Data were collected through observation and then analyzed using the Chi-square test. The results of the analysis showed p value = 0.000, so it could be interpreted that there was a difference in the fluency of breastfeeding between the treatment group and the control group. Furthermore, it was concluded that Moringa leaf extract had an effect on the smoothness of breast milk in postpartum mothers.Keywords: moringa leaves; breast milk; postpartum ABSTRAK Dalam masa nifas, salah satu hal yang paling utama adalah bagaimana ibu nifas mampu mengeluarkan air susu ibu (ASI) dengan lancar. Tujuan penelitian ini adalah untuk menganalisis pengaruh ekstrak daun kelor terhadap kelancaran ASI pada ibu postpartum di Puskesmas Kassi-Kassi. Rancangan penelitian ini adalah posttest only with control group. Sampel penelitian adalah 40 ibu postpartum yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui observasi lalu dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan nilai p = 0,000, sehingga bisa diinterpretasikan bahwa ada perbedaan kelancaran ASI antara kelompok intervensi dan kelompok kontrol. Selanjutnya disimpulkan bahwa ekstrak daun kelor berpengaruh terhadap kelancaran ASI pada ibu postpartum.Kata kunci: daun kelor; air susu ibu; postpartum